A probabilistic virtual process chain to quantify process-induced uncertainties in Sheet Molding Compounds. (15th January 2023) - Meyer, Nils; Gajek, Sebastian; Görthofer, Johannes; Hrymak, Andrew; Kärger, Luise; Henning, Frank; Schneider, Matti; Böhlke, Thomas
Abstract: The manufacturing process of Sheet Molding Compound (SMC) influences the properties of a component in a non-deterministic fashion. To predict this influence on the mechanical performance, we develop a virtual process chain acting as a digital twin for SMC specimens from compounding to failure. More specifically, we inform a structural simulation with individual fields for orientation and volume fraction computed from a direct bundle simulation of the manufacturing process. The structural simulation employs an interpolated direct deep material network to upscale a tailored SMC damage model. We evaluate hundreds of virtual specimens and conduct a probabilistic analysis of the mechanical performance. We estimate the contribution to uncertainty originating from the process-induced inherent random microstructure and from varying initial SMC stack configurations. Our predicted results are in good agreement with experimental tensile tests and thermogravimetric analysis. Graphical abstract: